CCNE1 stabilizes ANLN by counteracting FZR1-mediated the ubiquitination modification to promotes triple negative breast cancer cell stemness and progression - Sujuan Dai; Lin Li; Guangxiu Guo; Yun Peng; Huozhong Yuan; Juntao Li (Cell Death Discovery)
Abstract Triple-negative breast cancer (TNBC) is an aggressive subtype lacking targeted therapies. In this study, we aimed to investigate the pivotal role of cyclin E1 (CCNE1) in the onset and progression of TNBC using comprehensive bioinformatic analysis and functional validation. We found significantly elevated CCNE1 expression in TNBC tissues compared to normal, which correlated with poor prognosis. Functional assessments in vitro and in vivo demonstrated that knockdown of CCNE1 impaired the proliferative, migratory, and invasive capacities of TNBC cells, promoted apoptosis, and reduced tumorigenicity. Furthermore, CCNE1 sustains the stem-like properties of TNBC cells and fuels malignant progression through Anillin (ANLN). Mechanistically, CCNE1 interacted with ANLN and stabilized its protein levels by counteracting Fizzy-related protein 1 (FZR1)-mediated the ubiquitination modification in TNBC. Mutation of the ubiquitination site in ANLN affected CCNE1’s regulatory functions but not ANLN’s intrinsic properties. Taken together, these findings underscore the role of CCNE1 in promoting TNBC cell stemness and progression via competitive inhibition of FZR1-mediated ANLN ubiquitination. Consequently, targeting CCNE1 emerges as a promising therapeutic approach for breast cancer.